Effort-based decision making in schizotypy and its relationship with amotivation and psychosocial functioning - Chu, Ryan Sai Ting; Tong, Co Co Ho Yi; Wong, Corine Sau Man; Chang, Wing Chung; Tang, Wesley Chor Yin; Chan, Charlotte Cheuk Lok; Lui, Simon S. Y.; Hui, Lai Ming; Suen, Yi Nam; Chan, Kit Wa; Lee, Ho Ming; Chen, Eric Yu Hai (Frontiers in Psychiatry, 2023)
Introduction Suboptimal effort-based decision-making with reduced willingness to expend effort for high-probability/high-value reward is observed in schizophrenia patients and is related to diminished motivation, but is understudied in schizotypy. This study aimed to examine effort-allocation in schizotypy individuals and its association with amotivation and psychosocial functioning. Methods We recruited 40 schizotypy individuals and 40 demographically-matched healthy controls, based on Schizotypal Personality Questionnaire-Brief (SPQ-B) score (top and bottom 10% SPQ-B scores, respectively), from 2400 young people aged 15-24 years participating a population-based mental health survey in Hong Kong and examined effort-allocation using the Effort Expenditure for Reward Task (EEfRT). Negative / amotivation symptoms and psychosocial functioning were assessed by the Brief Negative Symptom Scale (BNSS) and the Social Functioning and Occupational Assessment Scale (SOFAS), respectively. Schizotypy individuals were categorized into high-amotivation and low-amotivation groups based on a median-split of BNSS amotivation domain score. Results Our results showed no main group effect (in either two or three-group comparison) on effort task performance. Three-group comparison analyses on selected EEfRT performance indices revealed that high-amotivation schizotypy individuals displayed significantly less increase in effortful options from low-value to high-value reward (reward-difference score) and from low-probability/low-value to high-probability/high-value reward (probability/reward-difference score) than low-amotivation individuals and controls. Correlation analyses demonstrated trend-wise significance between BNSS amotivation domain score and several EEfRT performance indices in schizotypy group. Schizotypy individuals with poorer psychosocial functioning tended to exhibit smaller probability/reward-difference score relative to other two groups. Discussion Our findings indicate subtle effort-allocation abnormalities in schizotypy individuals with high levels of diminished motivation, and suggest the link between laboratory-based effort-cost measures and real-world functional outcome.